Determinan Manajemen Keuangan Pribadi Pada Mahasiswa Aktif Di STIE Surakarta - Estiningtyas Widi Fitrianingrum; Dewi Ika Octavia (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research seeks to investigate the factors shaping personal finance management in enrolled students at STIE Surakarta, employing the Theory of Planned Behavior framework. It utilized a quantitative associative causal research design, drawing on a sample of 95 students chosen via simple random selection. Information was gathered through surveys and processed using multiple linear regression analysis. The findings reveal that financial literacy, Financial Technology, and Locus Of Control exert a significant positive influence on personal finance management, whereas a hedonistic lifestyle shows no notable impact. These outcomes underscore the necessity of bolstering financial literacy and promoting wise application of Financial Technology. Universities are encouraged to offer education on personal finance to foster students' awareness of finances, enabling them to responsibly balance essential needs with lifestyle choices.